Tropical and Parasitic Infections in the Intensive Care Unit - Feldman, Charles; Sarosi, George A. (Perspectives on Critical Care Infectious Diseases, 2005)
In the past, many tropical and parasitic infections were confined to tropical areas of the world located between the Tropic of Cancer and the Tropic of Capricorn. However, with the increase in air travel and tourism and the changing patterns of immigration, an increasing number of individuals are coming into contact with these infectious agents and transmission across the world has been enhanced. Tropical and Parasitic Infections in the Intensive Care Unit provides an international perspective on this topic and an overview of those infections that may cause critical illness. Charles Feldman, MB BCh., PhD, FRCP, FCP (SA) is a Professor of Pulmonology, Chief Physician and Head, Pulmonology Division of the University of the Witwatersrand Medical School in Johannesburg, South Africa. George Sarosi, MD is the Chief, Medical Service at Roudebush VA Medical Center and Professor of Medicine, Department of Internal Medicine at the Indiana University School of Medicine in Indianapolis, Indiana.